Catalyst for reforming methane mixed with other low-carbon alkanes as well as foaming preparation method and application of catalyst
By using alloys of Ni and synergistic components on γ-Al2O3 and combined with technical means of foaming, the problem of easy sintering and carbon deposits in the reforming reaction of methane mixed with other low-carbon alkanes is solved, and the high stability and long-term use ability of the catalyst are achieved.
Patent Information
- Application Number
- CN202411736013.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
AI Technical Summary
Existing catalysts are prone to sintering and carbon deposits in reforming reactions of methane mixed with other low-carbon alkanes, and are difficult to meet the needs of long-term use, especially under high temperature conditions.
The alloy composed of Ni and synergistic components is effectively dispersed on γ-Al2O3 by foaming method to prepare a catalyst with high stability. The method includes impregnating the carrier in a mixed solution containing nickel salt, synergistic metal salt and citric acid, and after drying and calcining, further impregnating the synergistic metal salt in the presence of citric acid to ensure uniform dispersion of the active and synergistic components.
The stability of the catalyst in the methane dry reforming reaction is improved. Especially when a small amount of ethane and propane are mixed, the stability of the catalyst is still good, extending its service life, and achieving efficient reforming of methane and other low-carbon alkanes.
Smart Images

Figure CN119701975A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, in particular to a catalyst for reforming methane mixed with other low-carbon alkanes and a foaming preparation method and application thereof. Background Art
[0002] Pollution prevention and control of greenhouse gases (carbon dioxide, methane, etc.) and low-carbon hydrocarbon volatile organic compounds (VOCs) is a major need for the country to protect the ecological environment and maintain the health of the people. The reforming reaction of methane mixed with other low-carbon alkanes is a strongly endothermic reaction process, which needs to be carried out under high temperature (750-850°C). The catalyst is extremely prone to sintering and carbon deposition, resulting in deactivation. Although there have been some studies, the life of the catalyst can be extended to a certain extent by adding precious metals and constructing catalyst carriers with special pore structures. For example, in order to address the problem of easy sintering of catalysts at high temperatures, Jones.G et al. found through first-principles calculations in Journal of Catalysis Volume: 259 Pages: 147-160, 2008 that precious metals such as Pt, Rh, Pd and Ru have better anti-carbon deposition performance, among which Ru and Rh have the strongest anti-carbon deposition ability. However, the cost of precious metals is high, and their large-scale synthesis is still difficult to meet the needs. Therefore, an ideal solution is needed. Summary of the invention
[0003] The present invention provides a catalyst for reforming methane mixed with other low-carbon alkanes, and a foaming preparation method and application thereof. An alloy consisting of Ni and a synergistic component is effectively dispersed on γ-Al2O3 by a foaming method, thereby improving the stability of the catalyst in a methane dry reforming reaction. Furthermore, under the condition of mixing with a small amount of ethane and propane, the stability of the catalyst can still be maintained, and the reaction is used to replace the separation process of methane and other low-carbon alkanes.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions: The foaming method of the catalyst for reforming methane mixed with other low carbon alkanes is as follows: step A or B: A. The carrier is immersed in a mixed solution containing nickel salt, synergistic metal salt and citric acid, and heated while stirring to evaporate the solvent; the catalyst is obtained after drying and calcining; B. The carrier is immersed in a mixed solution containing nickel salt and citric acid, and heated while stirring to volatilize the solvent; after drying and calcining, the carrier is immersed in a mixed solution containing a synergistic metal salt and citric acid, and heated while stirring to volatilize the solvent; after drying and calcining, the catalyst is obtained; The synergistic metal is one or more of lanthanum, cerium, zirconium or calcium.
[0005] Preferably, the carrier is γ-Al2O3 having pores larger than 2 nm.
[0006] Preferably, the nickel salt is one or more of nickel chloride, nickel nitrate, nickel sulfate or nickel carbonate; the synergistic metal salt is one or more of lanthanum sulfate, lanthanum nitrate, lanthanum carbonate, cerium phosphate, cerium sulfate, cerium nitrate, zirconium oxychloride, zirconium nitrate, calcium chloride and calcium nitrate; the solvent of the mixed solution is one or more of methanol, ethanol, ethylene glycol, water or glycerol.
[0007] Preferably, the total loading amount of nickel and the synergistic metal in the catalyst is 10-40%, and the mass ratio of nickel to the synergistic metal is 0.8-6:1.
[0008] Preferably, the pH value of citric acid is 0.4-2.6, more preferably 1-2.
[0009] Preferably, the mass of citric acid is 6-8 times the total mass of nickel and the synergistic metal.
[0010] Preferably, the drying conditions are: drying at 60-80°C for 20-24 hours; and the calcining conditions are: calcining at 600-1200°C in air for 2-4 hours.
[0011] The present invention also provides a catalyst for reforming methane mixed with other low-carbon alkanes, which is prepared by the above method.
[0012] The present invention also provides application of the catalyst, which is used to catalyze the reforming reaction of methane mixed with other low-carbon alkanes.
[0013] The other low carbon alkanes are C2-C6 chain alkanes. Preferably, the other low carbon alkanes are ethane and / or propane, and the reaction gas is a mixed gas of CH4, CO2, H2O, C2H6 and C3H8 in a volume ratio of 1:1-1.5:0.01-0.5:0-0.01:0-0.01, and C2H6 and C3H8 are not 0 at the same time.
[0014] Preferably, the catalyst is reduced and then used in a reforming reaction, the reaction temperature is 750-950°C, the reaction pressure is 0.8-1.2atm, and the reaction volume space velocity is 30000-90000mL / (gh).
[0015] Preferably, the conversion rate of other low-carbon alkanes is higher than 96%, the conversion rate of CH4 is higher than 86%, the conversion rate of CO2 is higher than 89%, and the activity reduction in a 1000-h long-cycle test does not exceed 10%.
[0016] Therefore, the beneficial effects of the present invention are as follows: (1) In the catalyst prepared by the present invention, the alloy composed of Ni and the synergistic component is effectively dispersed on γ-Al2O3, thereby improving the stability of the catalyst in the methane dry reforming reaction, and under the condition of mixing with a small amount of ethane and propane, the stability of the catalyst can still be maintained, and the reaction replaces the separation process of methane and other low-carbon alkanes; (2) The catalyst prepared by the citric acid foaming method can produce large pores, increase the carbon solubility, and thus reduce the deactivation rate caused by carbon deposition; (3) The catalyst prepared by the foaming method can improve the adsorption capacity of the carrier and the metal oxide for carbon dioxide, and can also make the active component and the synergistic component more evenly mixed, thereby showing excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the nitrogen adsorption isotherm of the carrier γ-Al2O3.
[0018] Figure 2 This is the XRD diagram of NiLa / γ-Al2O3 in Example 1.
[0019] Figure 3 It is the activity of the NiLa / γ-Al2O3 catalyst in Example 1 in a 1000h long-term test.
[0020] Figure 4 This is the SEM image of the catalyst NiZr / γ-Al2O3 in Example 2. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below through specific embodiments.
[0022] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0023] Example 1. A foaming method for preparing a catalyst for reforming methane mixed with other low-carbon alkanes Choose either method 1 or method 2.
[0024] Method 1. One-step impregnation method The method comprises the following steps: immersing a carrier in a mixed solution containing nickel salt, synergistic metal salt and citric acid, and heating while stirring to evaporate the solvent; after the solvent evaporates, taking out the solid, drying it at 60-80°C for 20-24h, and then roasting it at 600-1200°C in air for 2-4h to obtain a catalyst.
[0025] The present invention preferably uses γ-Al2O3 as a carrier. Alumina is a metal oxide suitable for use as a catalyst carrier. There are more than a dozen structures, the most common of which are α-Al2O3, γ-Al2O3, η-Al2O3, θ-Al2O3, δ-Al2O3, etc. Among them, γ-Al2O3 belongs to a face-centered cubic lattice and presents a defective spinel structure with high stability. The calcined γ-Al2O3 presents a porous structure and its specific surface area is greatly improved. Therefore, it has high chemical activity and adsorption capacity, and is widely used in hydrogenation reactions, desulfurization reactions, dehydrogenation reactions, condensation reactions, etc. For γ-Al2O3, its surface physicochemical properties play a vital role in the efficiency of the catalytic reaction. This is because the energy requirements of the exposed crystal faces of carriers with different morphologies are different, which directly affects the surface acidity of the carrier and its interaction with the active metal. The present invention selects γ-Al2O3 with a pore size of more than 2nm as a carrier. The nitrogen adsorption isotherm obtained by γ-Al2O3 is as follows: Figure 1 As shown in the figure, it can be seen that: γ-Al2O3 has a large specific surface area and has a hysteresis loop when p / p0>0.8, indicating that there are macropores larger than 2nm on the carrier, which is conducive to the dispersion of metal active species.
[0026] The nickel salt is a water-soluble nickel salt, preferably one or more of nickel chloride, nickel nitrate, nickel sulfate or nickel carbonate. The synergistic metal salt is a water-soluble salt of lanthanum, cerium, zirconium or calcium, preferably one or more of lanthanum sulfate, lanthanum nitrate, lanthanum carbonate, cerium phosphate, cerium sulfate, cerium nitrate, zirconium oxychloride, zirconium nitrate, calcium chloride and calcium nitrate.
[0027] The solvent of the mixed solution needs to be volatilized, preferably one or more of methanol, ethanol, ethylene glycol, water or glycerol with a low boiling point.
[0028] The pH value of citric acid is 0.4-2.6, and more preferably 1-2. The mass of citric acid is 6-8 times the total mass of nickel and synergistic metals. During the subsequent heating and stirring process, citric acid will expand and grow as the solvent evaporates, which is beneficial to forming a loosely dispersed structure of the metal salt of the precursor on the surface of γ-Al2O3. Nickel salts and synergistic metal salts themselves do not participate in the foaming reaction process, but are evenly distributed to the surface of γ-Al2O3 during the foaming process. Therefore, the amount of nickel salts and synergistic metal salts used will affect the structural morphology of the catalyst, thereby affecting the catalytic performance of the catalyst.
[0029] Method 2: Distributed impregnation method The method comprises the following steps: placing a carrier into a mixed solution containing nickel salt and citric acid for immersion, and heating while stirring to volatilize the solvent; after the solvent has completely evaporated, taking out the solid, drying it at 60-80°C for 20-24h, and then roasting it at 600-1200°C in the air for 2-4h, and then placing it into a mixed solution containing a synergistic metal salt and citric acid for immersion, and heating while stirring to volatilize the solvent; first drying it at 60-80°C for 20-24h, and then roasting it at 600-1200°C in the air for 2-4h to obtain a catalyst.
[0030] The carrier preferably contains γ-Al2O3 having a pore size of 2 nm or more.
[0031] The nickel salt is a water-soluble nickel salt, preferably one or more of nickel chloride, nickel nitrate, nickel sulfate or nickel carbonate. The synergistic metal salt is a water-soluble salt of lanthanum, cerium, zirconium or calcium, preferably one or more of lanthanum sulfate, lanthanum nitrate, lanthanum carbonate, cerium phosphate, cerium sulfate, cerium nitrate, zirconium oxychloride, zirconium nitrate, calcium chloride and calcium nitrate.
[0032] The solvent is preferably one or more of methanol, ethanol, ethylene glycol, water or glycerol with a low boiling point.
[0033] The pH value of citric acid is 0.4-2.6, more preferably 1-2. The mass of citric acid is 6-8 times the total mass of nickel and synergistic metals.
[0034] The step-by-step impregnation can first disperse the active metal nickel evenly and then better disperse the synergistic species.
[0035] 2. A catalyst for reforming methane mixed with other low-carbon alkanes is prepared by the above foaming method.
[0036] The catalyst carrier is γ-Al2O3, and the loaded active components are metal nickel and synergistic metal, and the synergistic metal is one or more of lanthanum, cerium, zirconium or calcium. The total loading amount of nickel and synergistic metal in the catalyst is 10-40%, and the mass ratio of nickel to synergistic metal is 0.8-6:1.
[0037] The catalyst prepared by the foaming method can produce large pores and increase the carbon solubility, thereby reducing the deactivation rate caused by carbon deposition; it can improve the adsorption capacity of the carrier and metal oxides for carbon dioxide, and can also make the active component nickel and the synergistic components more evenly mixed, thereby showing excellent performance.
[0038] 3. Application of catalysts for reforming methane mixed with other low carbon alkanes The catalyst is used for the reforming reaction of methane mixed with other low-carbon alkanes, comprising the following steps: (1) Catalyst reduction. The catalyst reduction method is not limited, and any reduction method in the prior art may be referred to. For example, in the embodiment, the above-mentioned catalyst is placed in a reducing atmosphere, the reduction temperature is 700-800°C, the reduction time is 1-3h, the reducing gas is a mixed gas of an inert gas and H2, the volume ratio is 0-9:1, the inert gas is one or more of nitrogen, argon or helium, and the volume space velocity of the reducing gas atmosphere is 30,000-90,000mL / (gh).
[0039] (2) Reforming reaction. The reduced catalyst is used for the reforming reaction of methane mixed with light alkanes, the reaction temperature is 750-950°C, the reaction pressure is 0.8-1.2atm, and the reaction volume space velocity is 30,000-90,000mL / (gh); other light alkanes include C2-C6 chain alkanes, which are mainly derived from natural gas, oil field associated gas, shale gas, petrochemical and by-products of oil refining processes. The present invention preferably uses ethane and / or propane. The reaction gas is preferably a mixed gas of CH4, CO2, H2O, C2H6 and C3H8 in a volume ratio of 1:1-1.5:0.01-0.5:0-0.01:0-0.01, and C2H6 and C3H8 are not 0 at the same time.
[0040] The conversion rate of other low-carbon alkanes is higher than 96%, the conversion rate of CH4 is higher than 86%, the conversion rate of CO2 is higher than 89%, and the activity reduction in the 1000h long-term test is no more than 10%. It shows that the catalyst prepared by the present invention is used for preparing synthesis gas in the reforming process of methane mixed with other low-carbon alkanes, and the reaction can be used to replace the separation process of methane and other low-carbon alkanes. In the prior art, similar catalysts are used for the catalytic reforming reaction of methane and carbon dioxide. The difficulty of the present invention is that compared with the catalytic reforming reaction of methane and carbon dioxide, the catalyst in the reforming reaction of methane mixed with other low-carbon alkanes is more prone to sintering and carbon deposition, resulting in deactivation, so the performance requirements of the catalyst are higher. The catalyst prepared by the present invention can reduce the activity by no more than 10% in the 1000h long-term test, which is a significant improvement.
[0041] The catalyst prepared by the present invention is not only used for methane mixed with low-carbon alkanes reforming reaction, but also can be used for methane dry reforming, wet reforming, partial oxidation reforming and the like.
[0042] Example 1 A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: 1.0g nickel nitrate hexahydrate is dissolved in water to obtain an impregnation solution, and 1.0g carrier γ-Al2O3 is impregnated. A citric acid solution with a pH of 0.4 (containing 1.3g citric acid) is added to the impregnation solution to assist in dissolution, and the solvent is evaporated while stirring and heating; after the solvent evaporates, the solid is taken out. The solid is first placed in a 60°C oven to dry for 24h, then roasted in air at 600°C for 2 hours, and then cooled to room temperature and placed in an aqueous solution containing 0.2g lanthanum nitrate hexahydrate, and a citric acid solution with a pH of 0.4 (containing 0.2g citric acid) is added to assist in dissolution, and the solvent is evaporated while stirring and heating; after the solvent evaporates, the solid is taken out. The solid is first placed in a 60°C oven to dry for 24h, then roasted in air at 600°C for 2 hours, and cooled to room temperature to obtain the catalyst NiLa / Al2O3, and the mass ratio of Ni:La:Al2O3 in the catalyst is 4:1:20.
[0043] The XRD patterns of γ-Al2O3 and catalyst NiLa / γ-Al2O3 are shown in Figure 2 As shown, it can be seen from the figure that there is an obvious NiO signal peak after loading NiLa.
[0044] The NiLa / Al2O3 catalyst obtained above was reduced in pure hydrogen gas at 700°C for 1 h at a volume space velocity of 30000 mL / (gh), and reacted at 750°C with a reaction gas composition of CH4, CO2, H2O, C2H6 and C3H8 in a volume ratio of 1:1.05:0.05:0.01:0 at a volume space velocity of 30000 mL / (gh) to test the catalyst performance. The results are as follows Figure 3 As shown in the figure, it can be seen that the average conversion rate of CH4 is 91%, the conversion rate of CO2 is 95%, and the conversion rate of other low-carbon alkanes is 98%. In addition, the activity of the NiLa / Al2O3 catalyst decreases by about 1% in the 1000h long-term test.
[0045] Example 2 A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g nickel sulfate hexahydrate in water to obtain an impregnation solution, add 1.0g carrier γ-Al2O3 for impregnation, add pH=1 citric acid solution (the solution contains 0.7g citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in a 100℃ oven for 2h, then roast in air at 1200℃ for 2h, cool to room temperature, put into an aqueous solution containing 0.2g zirconium nitrate, add pH=1 citric acid solution (the solution contains 0.2g citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in a 100℃ oven for 2h, then roast in air at 1200℃ for 2h, cool to room temperature to obtain the catalyst NiZr / Al2O3, the mass ratio of Ni:Zr:Al2O3 in the catalyst is 1.3:1:20.
[0046] The SEM image of the catalyst NiZr / Al2O3 is shown in Figure 4 As shown, it can be seen from the figure that the foamed catalyst has obvious macropores, which is conducive to the dispersion of active metals.
[0047] The NiZr / Al2O3 catalyst obtained above was reduced for 3h under 800℃ mixed gas (argon: hydrogen = 4:1) with a volume space velocity of 90000mL / (gh), and reacted at 850℃ with a volume ratio of CH4, CO2, H2O, C2H6 and C3H8 of 1:1.5:0.15:0:0.05 and a volume space velocity of 90000mL / (gh) to test the catalyst performance. The average conversion rate of CH4, CO2 and other low carbon alkanes was 92%, 94% and 98% respectively. The activity of NiLa / Al2O3 catalyst decreased by about 4% in the 1000h long cycle test.
[0048] Example 3 A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g of nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g of carrier γ-Al2O3 for impregnation, add a citric acid solution with a pH of 2 (the solution contains 0.8g of citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, cool to room temperature, put it in an aqueous solution containing 0.2g of cerium nitrate, add a citric acid solution with a pH of 2 (the solution contains 0.3g of citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:1.7:20.
[0049] The NiCe / Al2O3 catalyst obtained above was reduced at 750°C mixed gas (nitrogen: hydrogen = 1:1) for 2h, with a volume space velocity of 60000mL / (gh), and reacted at 950°C with a reaction gas CH4, CO2, H2O, C2H6 and C3H8 with a volume ratio of 1:1.2:0.1:0.005:0 and a volume space velocity of 60000mL / (gh) to test the catalyst performance. The obtained average conversion rate of CH4 was about 99%, the average conversion rate of CO2 was about 99%, the conversion rate of other low-carbon alkanes was about 99%, and the activity was reduced to 5% in a 1000h long-term test.
[0050] Example 4 The difference from Example 3 is that simultaneous impregnation is performed. The details are as follows: A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g nickel chloride hexahydrate and 0.2g cerium nitrate in water to obtain an impregnation solution, add 1.0g carrier γ-Al2O3 for impregnation, add pH=2 citric acid solution (the solution contains 1.1g citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80℃ for 24h, then roast in air at 800℃ for 2h, and cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:1.7:20.
[0051] Example 5 The difference from Example 3 is that the synergistic metal is La. A catalyst NiLa / Al2O3 is obtained, and the mass ratio of Ni:La:Al2O3 in the catalyst is 1.5:1.7:20.
[0052] Example 6 The difference from Example 3 is that the synergistic metal is Zr. A catalyst NiZr / Al2O3 is prepared, and the mass ratio of Ni:Zr:Al2O3 in the catalyst is 1.5:1.7:20.
[0053] Example 7 The difference from Example 3 is that the synergistic metal is Ca. A catalyst NiCa / Al2O3 is prepared, and the mass ratio of Ni:Ca:Al2O3 in the catalyst is 1.5:1.7:20.
[0054] Example 8 The difference from Example 3 is that the volume ratio of the reaction gases CH4, CO2, H2O, C2H6 and C3H8 is 1:1.2:0.1:0.005:0.005. The specific composition is as follows: A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g of nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g of carrier γ-Al2O3 for impregnation, add a citric acid solution with a pH of 2 (the solution contains 0.8g of citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, cool to room temperature, put it in an aqueous solution containing 0.2g of cerium nitrate, add a citric acid solution with a pH of 2 (the solution contains 0.3g of citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:1.7:20.
[0055] The NiCe / Al2O3 catalyst obtained above was reduced at 750°C mixed gas (nitrogen: hydrogen = 1:1) for 2h, with a volume space velocity of 60000mL / (gh), and reacted at 950°C with a reaction gas CH4, CO2, H2O, C2H6 and C3H8 with a volume ratio of 1:1.2:0.1:0.005:0.005, and a volume space velocity of 60000mL / (gh) to test the catalyst performance. The average conversion rate of CH4 obtained was about 86%, the average conversion rate of CO2 was about 89%, the conversion rate of other low-carbon alkanes was about 96%, and the activity was reduced to 5% in a 1000h long-term test.
[0056] Example 9 The difference from Example 3 is that the amount of citric acid used is lower than the preferred range. A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g of nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g of carrier γ-Al2O3 for impregnation, add a pH=2 citric acid solution (the solution contains 0.3g citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature, put it in an aqueous solution containing 0.2g cerium nitrate, add a pH=2 citric acid solution (the solution contains 0.3g citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:1.7:20.
[0057] Example 10 The difference from Example 3 is that the amount of citric acid used is higher than the preferred range. A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g carrier γ-Al2O3 for impregnation, add pH=2 citric acid solution (the solution contains 1.0g citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature and put it in an aqueous solution containing 0.2g cerium nitrate, add pH=2 citric acid solution (the solution contains 0.5g citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:1.7:20.
[0058] Comparative Example Comparative Example 1 The difference from Example 3 is that citric acid was not added.
[0059] Comparative Example 2 The difference from Example 3 is that the mass ratio of nickel to synergistic metal is 0.5:1, which is lower than the preferred range of 0.8-6:1. Specifically, a foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes comprises the following steps: Dissolve 0.3g of nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g of carrier γ-Al2O3 for impregnation, add a citric acid solution with a pH of 2 (the solution contains 0.8g of citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, cool to room temperature, put it in an aqueous solution containing 7.0g of cerium nitrate, add a citric acid solution with a pH of 2 (the solution contains 0.3g of citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an oven at 80°C for 24h, then roast in air at 800°C for 2 hours, and cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:3:20.
[0060] Comparative Example 3 The difference from Example 3 is that the mass ratio of nickel to the synergistic metal is 8:1, which is higher than the preferred range of 0.8-6:1.
[0061] The details are as follows: A foaming method for preparing a catalyst for a reforming reaction of methane mixed with other low-carbon alkanes, the steps are as follows: Dissolve 0.3g of nickel chloride hexahydrate in water to obtain an impregnation solution, add 1.0g of carrier γ-Al2O3 for impregnation, add a pH=2 citric acid solution (the solution contains 0.8g citric acid) to the impregnation solution to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature, put it in an aqueous solution containing 0.5g cerium nitrate, add a pH=2 citric acid solution (the solution contains 0.3g citric acid) to assist dissolution, stir and heat to evaporate the solvent; after the solvent evaporates, take out the solid. First dry the solid in an 80℃ oven for 24h, then roast in 800℃ air for 2 hours, cool to room temperature to obtain the catalyst NiCe / Al2O3, the mass ratio of Ni:Ce:Al2O3 in the catalyst is 1.5:0.2:20.
[0062] Performance Testing The catalytic performance data of the catalysts prepared in various examples and comparative examples are summarized in the following table.
[0063] Except for Examples 1, 2, and 8, the catalyst reduction and reforming reactions of other Examples and Comparative Examples are the same as those of Example 3, specifically: the above-obtained catalyst is reduced at 750°C under a mixed gas (nitrogen: hydrogen = 1:1) for 2 h with a volume space velocity of 60,000 mL / (gh), and reacted at 950°C with a reaction gas CH4, CO2, H2O, C2H6 and C3H8 having a volume ratio of 1:1.2:0.1:0.005:0 and a volume space velocity of 60,000 mL / (gh) to test the catalyst performance.
[0064] As can be seen from the above table, the catalysts prepared by the embodiments of the present invention have excellent catalytic performance and anti-deactivation performance when used for methane mixed with other low-carbon alkanes reforming reaction. In the prior art, similar catalysts are used for catalytic reforming reactions of methane and carbon dioxide. The difficulty of the present invention is that, compared with the catalytic reforming reaction of methane and carbon dioxide, the catalysts in the reforming reaction of methane mixed with other low-carbon alkanes are more prone to sintering and carbon deposition, leading to deactivation, so the performance requirements of the catalyst are higher. The catalyst prepared by the present invention can reduce the activity by no more than 10% in a 1000h long cycle test, which is a significant improvement.
[0065] Compared with Example 3: (1) Example 4 adopts simultaneous impregnation, and the catalytic performance is reduced, because the step-by-step impregnation can first disperse the active metal nickel evenly and then better disperse the synergistic species.
[0066] (2) Examples 5-7 respectively selected different synergistic metals, and the catalytic performance was different, indicating that different synergistic metals have a great influence on the catalyst performance.
[0067] (3) Comparative Example 1 does not have citric acid, that is, the foaming method is not used, and the catalytic performance is significantly reduced, because the foaming method has the ability to produce large pores, increase carbon dissolving capacity, thereby reducing the deactivation rate caused by carbon deposition; and the catalyst prepared by the foaming method can improve the adsorption capacity of the carrier and the metal oxide for carbon dioxide, and can also make the active component and the synergistic component more evenly mixed, thereby showing the advantages of excellent performance. Of course, the amount of citric acid used also affects the catalytic performance of the catalyst. In Example 9, the citric acid is too little, and the activity will be slightly reduced. In Example 10, the citric acid is too much, and the catalyst will expand greatly in volume during the drying and calcination process, which also affects the catalyst performance.
[0068] (4) The ratio of nickel to synergistic metal in Comparative Examples 2 and 3 is not within the preferred range, and the catalytic performance is reduced. This is because if the synergistic metal is too little, the active species will be less; if the synergistic metal is too much, the specific surface area exposed by the active species will be affected, thereby reducing the catalytic activity.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A foaming method for preparing a catalyst for reforming methane mixed with other light alkanes, characterized in that: Step A or B: A. The carrier is immersed in a mixed solution containing nickel salt, synergistic metal salt and citric acid, and heated while stirring to evaporate the solvent; the catalyst is obtained after drying and calcining; B. The carrier is immersed in a mixed solution containing nickel salt and citric acid, and heated while stirring to volatilize the solvent; after drying and calcining, the carrier is immersed in a mixed solution containing a synergistic metal salt and citric acid, and heated while stirring to volatilize the solvent; after drying and calcining, the catalyst is obtained; The synergistic metal is one or more of lanthanum, cerium, zirconium or calcium.
2. The foaming method according to claim 1, characterized in that: The nickel salt is one or more of nickel chloride, nickel nitrate, nickel sulfate or nickel carbonate; the synergistic metal salt is one or more of lanthanum sulfate, lanthanum nitrate, lanthanum carbonate, cerium phosphate, cerium sulfate, cerium nitrate, zirconium oxychloride, zirconium nitrate, calcium chloride and calcium nitrate; the solvent of the mixed solution is one or more of methanol, ethanol, ethylene glycol, water or glycerol.
3. The foaming method according to claim 1, characterized in that: The total loading amount of nickel and synergistic metal in the catalyst is 10-40%, and the mass ratio of nickel to synergistic metal is 0.8-6:
1.
4. The foaming method according to claim 1, 2 or 3, characterized in that: The mass of citric acid is 6-8 times the total mass of nickel and synergistic metals.
5. The foaming method according to claim 1, characterized in that: The drying conditions are: 60-80 ℃ for 20-24h; the calcination conditions are: 600-1200 ℃ in air for 2-4h.
6. A catalyst for reforming methane mixed with other low-carbon alkanes, characterized in that: The foaming method is prepared by any one of claims 1 to 5.
7. Application of the catalyst for reforming methane mixed with other low carbon alkanes, characterized in that: The catalyst prepared by the foaming method according to any one of claims 1 to 5 is used to catalyze the reforming reaction of methane mixed with other low-carbon alkanes.
8. The use according to claim 7, characterized in that: Other low-carbon alkanes are ethane and / or propane, and the reaction gas is a mixed gas of CH4, CO2, H2O, C2H6 and C3H8 in a volume ratio of 1:1-1.5:0.01~0.5:0~0.01:0~0.01, and C2H6 and C3H8 are not 0 at the same time.
9. The use according to claim 7 or 8, characterized in that: The catalyst is reduced and used in reforming reaction, the reaction temperature is 750-950 °C, the reaction pressure is 0.8-1.2 atm, and the reaction volume space velocity is 30000-90000 mL / (gh).
10. The use according to claim 7, characterized in that: The conversion rates of other low-carbon alkanes are higher than 96%, the CH4 conversion rate is higher than 86%, the CO2 conversion rate is higher than 89%, and the activity reduction does not exceed 10% in the 1000 h long-term test.